2023
DOI: 10.1159/000533140
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using the Global Tales Protocol to Elicit Personal Narratives in 10-year-Old Children in Ireland

Rena Lyons,
Stanislava Antonijevic-Elliott,
Sophie Barbotin
et al.

Abstract: Introduction. This small-scale study explored the feasibility of the Global TALES protocol in eliciting personal narratives in typically developing monolingual Irish children, using the online Zoom platform. We investigated children’s performance on measures of productivity (total number of utterances; total number of words) and syntactic complexity (MLU in words). We also documented the topics children talked about in response to the six emotion-based prompts contained in the Global TALES protocol. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The first three articles of this special issue report on the feasibility of using the Global TALES protocol with children from Iceland [5], Turkey [6], and Ireland [7]. Despite large individual variability in language productivity and semantic diversity within each language group, all three studies found that all six prompts were successful in eliciting personal narratives from most of the children.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first three articles of this special issue report on the feasibility of using the Global TALES protocol with children from Iceland [5], Turkey [6], and Ireland [7]. Despite large individual variability in language productivity and semantic diversity within each language group, all three studies found that all six prompts were successful in eliciting personal narratives from most of the children.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
“…Maviş and Yaşar-Gündüz [6] assessed ten 7-year-old and ten 10-year-old Turkish-speaking children and reported that all children produced a response to all of the prompts. Finally, Lyons et al [7] collected personal narrative samples from 19 ten-year-old English-speaking Irish children and found that the six protocol prompts were successful in eliciting stories from 84% of the children, with only one child declining to respond to three of the six prompts.…”
Section: An Overview Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations